Preservation Strategies for Archives at the Archive Depot of Malang City Public Library and Archives Office - Faedah, Agil Rizki; Ulum, Mochamad Chazienul (Manunggal Halim Jaya, 2025)
Archive preservation plays an important role in an organization's preservation and accessibility of documents with historical, legal, administrative, and cultural values for future generations. The problem addressed in this study is how the Archive Depot of Malang City Library and Archives Office ensures the preservation of the archives it manages. This study aims to identify and analyze the preservation strategies of archives implemented in the Archive Depot of Malang City Library and Archives Office. The method used in this study was a case study with a qualitative approach. The data collection techniques used were observation, interviews, and documentation. This study used a theory of preservation strategy by Sari & Putranto (2023). The results of the study showed that there are three main strategies in maintaining archive preservation. First, the storage environment is managed by maintaining the room temperature according to the standard, using appropriate storage media, such as roll-o-pack shelves and acid-free materials, and controlling humidity using silica gel. Second, preventing damage from external factors is implemented through fumigation, disinfectant spraying, camphorization, proper air circulation, and disaster mitigation training for archivists. Third, the implementation of technology is carried out through archive digitalization, storage on the digital platform e-Arsip (a digital-based electronic archive management system in the institution environment) and SIKN/JIKN (National Archive Information System and Network managed by ANRI as a platform for national archive integration and access), and improving the quality of archive visuals through a photo editing application. Through these strategies, archive institutions such as the Archive Depot of Malang City Library and Archives Office contribute to building a solid foundation for preserving the nation's collective memory and providing opportunities for inclusive and sustainable information access.